(3LRA ajg ahGFO ef MOjK MfHd GHf ESMGb Hf MfHds - (3MfHd Hf ESMGb Hf MfHd Hf gdGd GdTjHGfqj, CHh Ydj,J (B273 (3g` s
(3ChdgG (B:s
(3obQjA Ydi GdTjN GdUGdM CHj GdMSjf GdUjQai bQCg Ydjg hCfG CSeY GNHQce GHh Ydi GdMSjf Hf CMeO Hf GHQGgje Hf TGOGf s
(3BNQgG (B:s
(3MOKfG MfHd bGd eSde Hf GHQGgje bGd MOKfG Yf GdMSf Yf CHj gQjQI bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3ef bQC jGSjf ai djdI ZaQ dg (B) (3GdMeO ddg hefg s
(3GdfSNI HgG MhGTs
(3HBNQg SeGYGJ cKjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B86s
Keywords: (3GdMOjK h GdeUWdMs